METODE PROFILE MATCHING UNTUK DIAGNOSA GANGGUAN PENCERNAAN PADA ANAK - Indah Purwitasari Ihsan; Muh Sakir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Profile matching is one of the methods in the Decision Support System, but in this study the profile matching method is used for expert systems, namely for diagnosing digestive disorders in children aged 0 to 7 years, the input data is symptom data while the output is in the form of diagnosis results in the form of a percentage of types of disorders. digestion. The process of profile matching is to determine the weight of the criteria for each symptom, create a knowledge base/ideal profile, determine the weight of the gap, determine the core factor and secondary factor, calculate the gap for each input symptom with the symptoms in the knowledge base, determine the weight of each gap, calculate the core score factor and secondary factor, ranking with a weight of 60% core factor and 40% secondary factor. The results of the study show that the profile matching method can be used to create an expert system for diagnosing digestive disorders in children with an accuracy value of 82%.